Implementasi Nilai-Nilai Aqidah Ahlussunnah wal Jamaah dalam Perspektif Al-Qur’an - Muhammad Khozin; Abdul Ghaffar; Mohd Arifullah; Nia Nursaktila (Kartika: Jurnal Studi Keislaman, 2026)
Aqidah is the heart's conviction of truth. Aqidah serves as a religious basis to straighten and strengthen faith in Allah. This study examines the values of aqidah from the perspective of the Qur'an. The background of this study is that deviations from aqidah in Islam arise due to several factors, such as ignorance of religious knowledge, attitudes of ta'ashub or fanaticism passed down from generation to generation, thus justifying wrong behavior. These various forms of deviation generally indicate weak faith in Allah. This study identifies the understanding of the aqidah of Ahlussunnah wal Jamaah, links the understanding of Aswaja with the Qur'an, and analyzes its social and religious implications. This study uses an analytical method of analyzing Quranic texts. The type of research is library research, while the data analysis technique is conducted through document review. The object of this research is the values of faith. The research subjects are Ahlusunnah Waljamaah. Data collection was carried out using Kollelksil Dolkumeln, Analilsils Ilsil Dolkumeln. The results of the author found that: The values of Ahlussunnah wal Jamaah are in line with the teachings of the Qur'an which guide humans to think diversely, avoid excessive attitudes (at-tawassut), uphold intelligence, honesty, and justice (al-i'tidal), be tolerant (at-tasamuh), and apply a balance of service and devotion (at-tawazun). In addition, these values prevent evil and encourage good deeds (amar ma'ruf nahi munkar). Finally, the author recommends to readers, the Indonesian people understand the values of faith so that there is no deviation from faith